High energy X-ray diffraction and IR spectroscopy of Pt/Al2O3 during CO oxidation in a novel catalytic reactor cell. (3rd April 2017) - Marchionni, Valentina; Kambolis, Anastasios; Nachtegaal, Maarten; Kröcher, Oliver; Ferri, Davide
Abstract: The operando methodology dictates not only that catalysts are analysed during reaction while activity and selectivity are monitored by analytical methods, but also that the cell in which the measurement is carried out performs as a catalytic reactor. A cell (Chiarello et al., Rev. Sci. Inst. 85 (2014) 074102) used to conduct spectroscopy and diffraction measurements under operando conditions was tested for CO oxidation on a 2 wt% Pt/Al2 O3 catalyst and compared with measurements in a conventional quartz catalytic reactor to demonstrate its suitability to derive kinetic data. High energy X-ray diffraction data were collected during alternate CO and O2 pulses under differential conditions to demonstrate the extent of loss of order of the Pt particles upon exposure to the O2 pulse. The presence of a surface oxide species places the catalyst in a higher activity regime compared to the fully reduced one. Abstract :